2012
DOI: 10.6061/clinics/2012(03)03
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in patients with chronic hepatitis C virus genotype 1 infection who do not have obesity or type 2 diabetes

Abstract: OBJECTIVE:The individual components of metabolic syndrome may be independent predictors of mortality in patients with liver disease. We aimed to evaluate the prevalence of metabolic syndrome and its related components in hepatitis C virus–infected patients who are not obese and do not have type 2 diabetes.METHODS:This cross-sectional study included 125 patients infected with hepatitis C virus genotype 1. Metabolic syndrome was defined according to the International Diabetes Federation. Anthropometric data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
12
1
1
Order By: Relevance
“…The severity of HBV-and HCV-related liver diseases and rate of disease progression are impacted by age, gender, host factors, exposure to alcohol, coinfections, viral genotype and MS (11). In addition, the individual components of MS might also be independent predictors of morbidity/mortality in patients with liver diseases, such as those caused by HBV or HCV (12). A multitude of other studies have also reported that HCV is a risk for MS and/or various individual components of MS, including IR as cited in Negro and, more recently, the review articles by HBsAg positive rate (%) 15 Sheikh et al and Del Campo and Romero-G omez (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of HBV-and HCV-related liver diseases and rate of disease progression are impacted by age, gender, host factors, exposure to alcohol, coinfections, viral genotype and MS (11). In addition, the individual components of MS might also be independent predictors of morbidity/mortality in patients with liver diseases, such as those caused by HBV or HCV (12). A multitude of other studies have also reported that HCV is a risk for MS and/or various individual components of MS, including IR as cited in Negro and, more recently, the review articles by HBsAg positive rate (%) 15 Sheikh et al and Del Campo and Romero-G omez (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Perls’ staining with score of 0–4 was applied to assess hepatic siderosis. Based on data from the insulin secretion and fasting glucose analyses, the HOMA-IR (homeostasis model assessment of insulin resistance) index of the patients was calculated and patients who presented HOMA-IR ≥3.0 were considered to have insulin resistance [16, 17]. …”
Section: Methodsmentioning
confidence: 99%
“…Hepatitis C virus (HCV) threatens human health; an estimated >185 million infected persons globally (Hanafiah, Groeger, Flaxman, & Wiersma, 2013) are at risk of developing hepatic diseases, including hepatitis, liver cirrhosis, and hepatocellular carcinoma (Sanyal, Yoon, & Lencioni, 2010), as well as metabolic disorders, including insulin resistance (Milner et al, 2010) and metabolic syndrome (Oliveira et al, 2012). The incidence of HCV infection has been in decline since 1990s, but the burden of HCV-related advanced disease will continue to rise for the next two decades (Razavi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%